Behavioral Analysis of the Statute for People with Disabilities by the Judiciary: Punishments for Ableist Acts in Schools - Rodrigues, Meigan Sack; Oliveria-Castro Neto, Jorge Mendes de (Perspectivas em Análise do Comportamento, 2025)
This study examines the application of the Statute for People with Disabilities (Law No. 13,146/2015) by the Brazilian Judiciary in cases of ableism within the school environment, specifically in the Federal District. Ableism, defined as discriminatory practices and beliefs against people with disabilities, manifests in schools through actions such as denial of enrollment, lack of curricular adaptations, and insufficient support, which undermines the right to inclusive education. The research analyzed a sample of 100 decisions from the Court of Justice of the Federal District and Territories, focusing on judicial decisions that address demands from neurodivergent students for specialized monitoring, school adaptations, and anti-discrimination measures. Quantitative and inferential analyses were applied to identify the most frequently used legal arguments, as well as the importance of documentary evidence in proving students’ needs. The results indicated an inconsistent application of Law No. 13,146/2015, with variations in decisions and in the frequency of penalties. Legal reasoning and presented documentation influence case outcomes. This study highlights the importance of consistency in judicial decisions and the need for improved implementation of inclusive policies in schools to ensure that the rights of people with disabilities are upheld in educational institutions.